A Clinical Review of the Management of Frostbite. Issue 1 (1st March 2011) - Grieve, AW; Davis, P; Dhillon, S; Richards, P; Hillebrandt, D; Imray, Chris
Abstract : Frostbite is a thermal injury that can occur when temperatures drop low enough for tissue to freeze. On rewarming the tissues, an inflammatory process develops which is often associated with tissue loss. The extent of the tissue loss reflects the severity of the cold exposure and includes factors such as temperature, duration, wind chill, altitude, and systemic hypothermia. This review discusses the epidemiology, the pathophysiological processes involved, and the clinical management of frostbite injuries. Practical advice is given on both the field and hospital management and how to seek expert advice from remote situations. The review also discusses newer developments in frostbite treatment such as intra-vascular thrombolysis and adjunctive treatments such as the use of intravenous vasodilators.